807 A multicenter open-label phase I/lb study of SO-C101 as monotherapy and in combination with pembrolizumab in patients with selected advanced/metastatic solid tumors. (9th November 2020) - Marabelle, Aurelien; Champiat, Stephane; Garralda, Elena; Hernando, Alberto; Janku, Filip; Raina, Anjali; Sachse, Richard; Bechard, David; Krasnopolskaya, Inna; Ferrara, Stefano; LoRusso, Patricia
Abstract : Background: IL-15 is a member of the common y-chain family of cytokines that shares functional activities with IL-2. SO-C101is a superagonist fusion protein of IL-15 and the IL-15 receptor α sushi+ domain. SO-C101 stimulates the proliferation and the cytotoxic activity of NK cells and memory CD8+ T cells. In pre-clinical studies SO-C101 promoted expansion and activation of human, murine and cynomolgus monkey NK and CD8+ T cells. NK and CD8+ T cell activation correlated with potent monotherapy anti-cancer activity of SO-C101 in metastatic and solid tumor models. The combination of an anti-PD-1 or of anti-cancer monoclonal antibodies with SO-C 101 augmented the anti-tumor responses in mouse models. First clinical study was initiated in June 2019 to investigate SO-C101 as monotherapy and in combination with pembrolizumab. Methods: The phase 1/1 b study currently on-going is a multicenter, open-label, dose escalation study for patients with selected advanced/metastatic solid tumors. The study consists of 2 parts: Part A - dose escalation of SO-C101 as monotherapy; Part B - dose escalation of SO-C101 in combination with pembrolizumab. Study objectives are to define the maximum tolerated dose (MTD) and/or recommended phase 2 dose (RP2D) of SO-C101 in both parts. Results: As of September 22nd, 19 subjects were treated in part A in 6 escalating dose levels, and 3 subjects were treated in part B, at dose level 1. SO-C101 was well tolerated. No DLT was observed, the main AEs related to SO-C101 were injection site reactions, fever, chills, flu-like syndrome, all G1- G2, and transient lymphopenia in 5 subjects, Grade 2 to 4, all resolved within few days. Preliminary PK results showed the PK profile to be dose-proportional, with a Tmax of approx. 5 – 6 hours after administration and T½ approx. 4 hours. Preliminary PD analysis showed dose dependent NK and CD8+ T cell activation. A preliminary efficacy signal has been observed in a patient refractory to anti-PD1 therapy, who showed a RECIST PR with initial 20% shrinkage of target lesions at 6 weeks and 49% shrinkage at 12 weeks on CT-scans. Conclusions: To date, SO-C101 has been well tolerated, with a manageable toxicity and encouraging signs of clinical activity. The study will proceed to reach a RP2D in both monotherapy and combination with Pembrolizumab. Expansion of the study in selected indications is warranted. Trial Registration https://clinicaltrials.gov/ct2/show/NCT04234113 ?term=sotio&draw=3&rank=12 The study was approved to proceed by FDA – IND 140011 -and by the sites ECs. Ethics Approval: The NCT04234113 clinical trial was approved by each investigational site health agency and ethical committee. Consent: Written informed consent of patients was obtained prior enrollment in the NCT04234113 clinical trial.